2006
DOI: 10.1099/vir.0.81618-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proteinase K-resistant N- and C-terminally truncated PrP in Nor98 atypical scrapie

Abstract: An increasing number of scrapie cases with atypical characteristics, designated Nor98, have recently been recognized. Here, the proteinase K (PK)-resistant prion protein (PrP) fragments from two Swedish cases of Nor98 atypical scrapie have been characterized. The prominent, fast-migrating band in the distinct Nor98 Western immunoblot electrophoretic profile was determined to be of 7 kDa in size and was accordingly designated Nor98-PrP7. The antigenic composition of Nor98-PrP7, as assayed by a panel of anti-PrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 45 publications
6
56
1
Order By: Relevance
“…Recently, three published biological studies have given a more precise description of newly identified fragments. The atypical/Nor98 scrapie isolates display after proteinase K treatment a distinct multiple band pattern, with a fast migrating band reported to be around 11-12 kDa [2, 5, 18] or 7-8 kDa [24,31] in size. These differences between the atypical/Nor98 scrapie and the classical scrapie isolates are illustrated in Figure 2. It is noteworthy that, in contrast to what has been reported in human TSE, the same multiple band Western blot profile is observed independently of the brain region [2,31].…”
Section: Identification Of New Prp Sc Fragmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, three published biological studies have given a more precise description of newly identified fragments. The atypical/Nor98 scrapie isolates display after proteinase K treatment a distinct multiple band pattern, with a fast migrating band reported to be around 11-12 kDa [2, 5, 18] or 7-8 kDa [24,31] in size. These differences between the atypical/Nor98 scrapie and the classical scrapie isolates are illustrated in Figure 2. It is noteworthy that, in contrast to what has been reported in human TSE, the same multiple band Western blot profile is observed independently of the brain region [2,31].…”
Section: Identification Of New Prp Sc Fragmentsmentioning
confidence: 99%
“…Klingeborn et al [24] used harsher proteinase K conditions, which, together with the applied antibodies, might explain at least partially the differences between the two studies. One of the isolates of the Swedish isolate has been analysed with the method used by Arsac et al [2] (TeSeE Western blot, Bio-Rad), giving in these conditions a Western blot profile which was identical to the Norwegian Nor98 isolates.…”
Section: Deglycosylation Experimentsmentioning
confidence: 99%
See 3 more Smart Citations